The republican epic of Spain in the work of Almudena Grandes - Angulo, Sablina (2024)
Almudena Grandes (1960 -2021), renowned Spanish writer, winner of the National Prize of Narrative (2018), has bequeathed us extraordinary works of fiction that include real stories based on a great work of documentation. Among her works, in which she links sociology, politics, history and literature, stands out "El corazón helado", a novel that narrates the social conflict in Spain, still unresolved, as a consequence of the coup d'état against the Republican government, in 1936. All of this is narrated, in literary terms, in the romance between Álvaro Carrión and Raquel Fernández. He, Álvaro, son of an adventurer who enlisted in the Spanish detachment, "Blue Division", to support Hitler in the invasion of the Soviet Union and who, like many Francoists in the post-war period, made a great fortune by appropriating the goods and properties of Republican families. She, Raquel, granddaughter of republicans vexed by Franco's regime and refugees in France, country where they would fight against Nazism in World War II.